Power analysis applying the instantaneous complex power analytical expressions on a RL symmetrical three-phase system - Milanez, Dalgerti Lelis [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1997)
This paper enhances some concepts of the Instantaneous Complex Power Theory by analyzing the analytical expressions for voltages, currents and powers developed on a symmetrical RL three-phase system, during the transient caused by a sinusoidal voltage excitation. The powers delivered to an ideal inductor will be interpreted, allowing a deep insight in the power phenomenon by analyzing the voltages in each element of the circuit. The results can be applied to the understanding of non-linear systems subject to sinusoidal voltage excitation and distorted currents.
Keywords: Mathematical transformations; Power inductors; Instantaneous complex power theory; Circuit theory